2019
DOI: 10.3390/rs11020117
|View full text |Cite
|
Sign up to set email alerts
|

Full-Waveform LiDAR Fast Analysis of a Moderately Turbid Bay in Western France

Abstract: In shoreline monitoring, only topo-bathymetric light detection and ranging (LiDAR) can map large corridors from aerial dunes to sandbanks in shallow water. Increasing turbidity masking the formation of 532 nm laser beam echoes on the sea bed makes this challenging. Full-waveform recording all the laser beam damping functions, a turbid water column can be seen as an accumulation of layers forming a single continuum and a distinction can be made between signals ending at the bottom down to a depth of 10 m. In pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…In addition to 3D topography, airborne LiDAR is also currently the best technique to obtain bathymetric data, which is crucial to coastal science but challenging to acquire through conventional terrestrial field surveys or boat-based acoustic hydrographic surveys. Launeau et al [14] used full-waveform LiDAR data to map the bathymetry of the sea bottom in moderately turbid bays. In the United States, the Army Corps of Engineers (USACE) utilizes Coastal Zone Mapping and Imaging LiDAR System (CZMIL) to map coastal zone bathymetry, topography, and other properties [15,16].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to 3D topography, airborne LiDAR is also currently the best technique to obtain bathymetric data, which is crucial to coastal science but challenging to acquire through conventional terrestrial field surveys or boat-based acoustic hydrographic surveys. Launeau et al [14] used full-waveform LiDAR data to map the bathymetry of the sea bottom in moderately turbid bays. In the United States, the Army Corps of Engineers (USACE) utilizes Coastal Zone Mapping and Imaging LiDAR System (CZMIL) to map coastal zone bathymetry, topography, and other properties [15,16].…”
Section: Related Workmentioning
confidence: 99%
“…The U.S. Geological Survey (USGS) has taken advantage of these new techniques to conduct shoreline change assessment with success [17][18][19]. Current studies concluded that the most restricting factor of LiDAR bathymetry is water clarity [14,16] and thus, it is important to conduct the flight during tidal and current conditions that minimize the water turbidity. Considering weather conditions, as well as budget restrictions, manned aircraft-based coastal surveys cannot be carried out frequently, thus preventing the quantification of coastal response to individual storms and rapid water level fluctuations.…”
Section: Related Workmentioning
confidence: 99%
“…ASDF_M and ASDF_A denote the point clouds generated from the signals detected by the maximum method with a fixed threshold and the adaptive threshold from the waveforms that are processed by ASDF. We also applied the method proposed in [25] which used a first derivative of a wide Gaussian filter to reduce the processing range of the waveform, and processed the waveforms in this range with normalization, multiple smoothing and three times derivation to increase the detection rate of the bottom signal. The point clouds generated from this method are referred to as dddNCFWF.…”
Section: Resultsmentioning
confidence: 99%
“…Richter et al [24] proposed an attenuation correction procedure to improve the detectability of water bottom signals. Launeau et al [25] proposed a waveform processing method including smoothing and edge enhancing to increase the detection rate of the bottom signal in moderately turbid water. The de-noising and signal-enhancing methods can improve the detection rate, but the detection accuracy is still limited by the waveform sampling interval, which may also require waveform decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring optical properties of water, estimating backscatter coefficient, detecting bubbles, internal waves, planktons, and schools of fish are other applications that have been studied by all types of LiDAR instruments [251], [255], [257], [269]. However, Bathymetric and 3D mapping applications are mainly limited to airborne LiDAR instruments [261], [270], [271]. Recently, the ICESat-2 spaceborne LiDAR has also attracted attention in such applications [272].…”
Section: B Applicationsmentioning
confidence: 99%